GP2015 as a promising therapy for rheumatoid arthritis. (3rd April 2018) - Fitton, John; Giollo, Alessandro; Buch, Maya H.
ABSTRACT: Introduction : Rheumatoid arthritis is a common inflammatory joint disease with a myriad of systemic manifestations. Over the last 20 years its treatment has been revolutionised by the introduction of a number of different biologic drugs, including the TNF-receptor Fc fusion protein, Etanercept. However, these drugs are expensive and their widespread use puts a financial burden on healthcare systems. As many biologic treatments begin to come off patent new 'biosimilar' versions are being developed which can lead to significant cost savings. GP2015 (Erelzi®) is the second biosimilar version of Etanercept which is licensed for the treatment of rheumatoid arthritis. Areas covered : We discuss the Chemistry, pharmacokinetics and pharmacodynamics of GP2015 in relation to reference Etanercept. Preclinical trials have shown pharmacokinetic equivalence between GP2015 and the reference drug. The recently completed Phase III, randomised, double blind EQUIRA study has shown equivalent efficacy and safety between GP2015 and Etanercept in patients with rheumatoid arthritis. Expert opinion : GP2015 has shown equivalent efficacy and safety to reference Etanercept. With a growing number of biosimilar medications becoming available and another biosimilar Etanercept already being widely prescribed it is likely to be the cost of the drug that will determine if it is used widely.